2012
DOI: 10.1016/j.jcf.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient indicators of a pulmonary exacerbation: Preliminary reports from school aged children map onto those of adults

Abstract: Child-reported indicators of a pulmonary exacerbation tend to map onto those reported by adults. These results provide the rationale for the development of a single scale for school age children and adults that could be sensitive to progressive stages of CF disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Interestingly, a recent study found that lack of appetite was one of the most common symptoms associated with the onset of an exacerbation in children and adults with CF suggesting that regularly assessing appetite as part of a symptom survey could give valuable insight into health status. 20 In our local setting, we observed that patient compliance/non-compliance influenced the speed of disease progression, treatment, and, ultimately, outcome. It is of particular interest that patients with the same genotype exhibit different levels of disease severity suggesting there are other factors at work.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, a recent study found that lack of appetite was one of the most common symptoms associated with the onset of an exacerbation in children and adults with CF suggesting that regularly assessing appetite as part of a symptom survey could give valuable insight into health status. 20 In our local setting, we observed that patient compliance/non-compliance influenced the speed of disease progression, treatment, and, ultimately, outcome. It is of particular interest that patients with the same genotype exhibit different levels of disease severity suggesting there are other factors at work.…”
Section: Introductionmentioning
confidence: 88%
“…18 This symptom cluster is similarly reported by adults and children with CF. 20 PROs are now believed to be an essential part of patient-centered care and have been used to evaluate drugs, to assess and track the effects and progress of a disease on different aspects of patients functioning and for developing individual treatment plans. 21,22 A well-established PRO, the Cystic Fibrosis Questionnaire-Revised Respiratory Symptoms Scale (CFQ-RRSS), has recently been used to evaluate respiratory symptoms in CF in order to establish the efficacy of inhaled antibiotics over 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Abbott (17) realizó un estudio en Gran Bretaña (UK) con 70 personas, comparando niños y ancianos en cuanto a los efectos indeseables durante las crisis de enfermedad respiratoria. En ambos, la falta de apetito relacionada a la disnea fue frecuente entre los participantes.…”
Section: Discusionesunclassified
“…20 When children with cystic fibrosis are interviewed about symptom improvement after exacerbations, they report, among other improvements, a sputum color change. 21 As self-assessment of sputum color by patients was demonstrated to be unreliable, 10 so there is a need for validated tools. Although the Sputum Color Chart previously demonstrated a good inter-rater reliability between doctors and subjects, 5 no study had previously investigated the intra-rater reliability for different health caregivers and the inter-rater reliability between different health professionals.…”
Section: Used Thementioning
confidence: 99%